The effects of weaning related stress on the emotional health of horses - Dwyer, Joanne (2025)
Domestic weaning processes have the potential to cause intense distress in both mares and foals particularly when the mare and foal are separated abruptly and isolated in a confined space. This distress can create patterns of emotional dysregulation that could have long-term welfare implications. In wild and semi-feral herds, the physical separation of foals from their mothers does not usually occur until they reach sexual maturity at 2-3 years old and go off to form their own herds. Physically separating foals from their mothers at 6 months old in domestic circumstances can cause a range of stress related behaviours such as stereotypies and increased vocalization and defecation during the weaning process. However, progressive separation, where mares and foals spend a brief time away from each other daily, can not only reduced the intense distress experienced by abrupt forms of separation but the health of the mares has shown to improve where progressive weaning separation appears to reduce the likelihood of mastitis. The aim of this thesis was to establish evidence to develop an equine weaning welfare assessment tool.